Mitochondrial Diseases - Taskin, Eylem; Guven, Celal; Sevgiler, Yusuf (IntechOpen, 2018)
Mitochondria are crucial organelles for any cell type. Mitochondria take responsibility for not only energy production but also regulation of cell death, also called apoptosis; calcium storage; and heat production. Therefore, mitochondrial disease is implicated in the mode of action of many harmful factors for cells such as drugs and environmental contaminants, dysfunction of the oxygen transport system, malnutrition, intense exercise, and genetic variations. This book presents up-to-date knowledge about mitochondrial disease and its complex relation to some diseases such as cardiac failure, cancer, and Alzheimer's and Parkinson's diseases. This book will, therefore, be essential for readers who are interested in life sciences, especially in medicine.